Implementasi Metode Jigsaw untuk Meningkatkan Partisipasi dan Pemahaman Siswa dalam Pembelajaran Aqidah Akhlak di MA NU Putri Buntet Pesantren - Bayanillah, Ahmad; Rifa'i, Muhadditsir; Muthoharoh, Muthoharoh (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2025)
One of the main challenges in teaching Aqidah Akhlak at MANU Putri Buntet Pesantren is the low level of student participation and lack of discipline in following the learning process. This condition negatively affects students’ understanding of the subject matter, which plays an essential role in shaping their character and moral values. The primary cause of this issue is the use of monotonous teaching methods that fail to actively engage students. As a solution, the Jigsaw method is implemented to encourage active student participation through a cooperative learning approach, where students work in groups, interact with one another, and take responsibility for understanding the material. This study employs a descriptive qualitative approach to describe the implementation of the Jigsaw method in Aqidah Akhlak learning and to analyze its impact on student participation and comprehension. Data were collected through observation, interviews, and documentation involving students from classes X.1, X.2, and X.3, as well as the subject teacher at MA NU Putri Buntet Pesantren. The research was conducted in four stages: planning, implementation, observation, and reflection, with data analyzed through reductive and descriptive techniques to provide a comprehensive picture of the Jigsaw method’s effectiveness. The findings indicate that the Jigsaw method enhances student participation through group discussions, role assignments, and presentations of their understanding. Furthermore, students' comprehension of Aqidah Akhlak improved alongside increased interaction and a stronger sense of responsibility during the learning process. Thus, the Jigsaw method can serve as an effective alternative for teachers to foster a more interactive, collaborative, and meaningful classroom learning environment.